Association between pulse pressure at discharge and clinical outcomes in patients with acute myocardial infarction: From the KAMIR‐Korean‐NIH registry. Issue 6 (23rd April 2019) - Park, Hyun Woong; Kang, Min Gyu; Kim, Kyehwan; Koh, Jin‐Sin; Park, Jeong Rang; Hwang, Seok‐Jae; Kim, Hye Ree; Jeong, Young‐Hoon; Ahn, Jong Hwa; Jang, Jeong Yoon; Kwak, Choong Hwan; Park, Yongwhi; et al.
Abstract: Pulse pressure (PP) is affected by arterial stiffness and is a predictor of cardiovascular events. However, value and utility of PP assessment in patients with acute myocardial infarction (AMI) remain less clear. We aimed to evaluate the association between PP and cardiovascular events in surviving patients with AMI at discharge. A total of 11 944 surviving patients with AMI at discharge from a Korean nationwide registry were included. Blood pressure was checked just before discharge. Noncardiac death and major adverse cardiovascular events (MACEs) including cardiac death, AMI, and stroke after discharge were analyzed. The median follow‐up duration was 368 (IQR 339, 388) days. The rate of MACEs and cardiac death was higher in groups with the lowest PP (PP < 20 mm Hg) and highest PP (PP ≥ 71 mm Hg) and lowest in the group with PP of 31‐40 mm Hg. With PP of 31‐40 mm Hg as reference, univariate analysis showed a U‐shaped association between the risk of MACEs (PP ≤ 20 mm Hg: hazard ratio [HR] 2.3; PP ≥ 71 mm Hg: HR 2.7) or cardiac death (PP ≤ 20 mm Hg: HR 2.6; PP ≥ 71 mm Hg: HR 3.1) and PP. In multivariate analysis, the curve changed from being U‐shaped to J‐shaped, and HR for PP ≥ 71 mm Hg (1.2 for MACEs and 1.4 cardiac death) decreased and HR for PP < 20 (2.1 for MACEs and 2.4 for cardiac death) did not significantly decrease after adjustment for cardiovascular risk factors. Our findings indicate that PP is a strong independent prognostic factor of MACEs and cardiac death in surviving patients with AMI. Low PP is a more significant independent predictor of MACEs and cardiac death than high PP in surviving patients after AMI.